2015
DOI: 10.11604/pamj.2015.22.156.7296
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of priority setting process and its implication on availability of emergency obstetric care services in Malindi District, Kenya

Abstract: IntroductionIn spite of the critical role of Emergency Obstetric Care in treating complications arising from pregnancy and childbirth, very few facilities are equipped in Kenya to offer this service. In Malindi, availability of EmOC services does not meet the UN recommended levels of at least one comprehensive and four basic EmOC facilities per 500,000 populations. This study was conducted to assess priority setting process and its implication on availability, access and use of EmOC services at the district le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…There are limited mechanisms of incorporating community values in the planning and budgeting processes. This finding is consistent with studies done in both HICs and LMICs . According to communitarian claims, it is not enough to just subject the community to the decisions made, they should be involved to the extent of determining how resources are allocated .…”
Section: Discussionsupporting
confidence: 89%
“…There are limited mechanisms of incorporating community values in the planning and budgeting processes. This finding is consistent with studies done in both HICs and LMICs . According to communitarian claims, it is not enough to just subject the community to the decisions made, they should be involved to the extent of determining how resources are allocated .…”
Section: Discussionsupporting
confidence: 89%
“…There was, however, a general consensus that the guidelines limited the ability of regions to set their own priorities ( Bukachi et al ., 2014 ; Gibson et al ., 2006 ; Maluka et al ., 2010a ; Maluka, 2011 ; Nyandieka et al ., 2015 ; Robinson et al ., 2012 ). For example, Nyandieka et al (2015) on assessment of priority setting implications on emergency obstetrics care (EMOC) found that Malindi district in Kenya, had limited freedom in setting priorities as the process is largely dependent on national level guidelines. In Mbarali district in Tanzania, Maluka et al (2010a) found that when district priorities conflicted with national priorities in the planning and budgeting process, the national priorities took precedence.…”
Section: Resultsmentioning
confidence: 99%
“…Ministry of Health (MoH) guidelines for health management committees [33] provide for participation in health planning process through representation of community members in order for them to represent community interests. The said representation has been found to be inadequate, as perceived by some of the in-charges of health facilities in Malindi [34]. Besides most community members do not know their representatives and do not discuss their needs before the representatives attend meetings to represent them.…”
Section: Discussionmentioning
confidence: 99%
“…One strategy suggested in the annual operations plan (AOP) [37] was to sensitize community through barazas, a strategy that is usually carried out by calling community meetings under the local administration to address emerging issues in the community. One of the weaknesses of this strategy is that usually the men send their wives to such meetings to represent them [34], thus leaving out the very people targeted by the health planners.…”
Section: Discussionmentioning
confidence: 99%